Flow management using natural instabilities - Floryan, J.M. (Archives of Mechanics, 2006)
Accidental introduction of a small disturbance into an unstable flow leads to a large change in the form of the motion, e.g., laminar-turbulent transition. We wish to explore this phenomenon in the design of flow management strategies. We want to modulate the flow using a small input of external energy in such a way that the flow evolves through a natural instability process to a new, more desirable form. This presentation is focused on the use of distributed surface roughness for such purposes.